2022
DOI: 10.1021/acs.est.2c01878
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Aerobic Methane Oxidation and Arsenate Reduction Contributes to Soil-Arsenic Mobilization in Agricultural Fields

Abstract: Microbial oxidation of organic compounds can promote arsenic release by reducing soil-associated arsenate to the more mobile form arsenite. While anaerobic oxidation of methane has been demonstrated to reduce arsenate, it remains elusive whether and to what extent aerobic methane oxidation (aeMO) can contribute to reductive arsenic mobilization. To fill this knowledge gap, we performed incubations of both microbial laboratory cultures and soil samples from arsenic-contaminated agricultural fields in China. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…In recent decades, progress has been achieved to understand the geochemical cycling and translocation of As and Cd from soil to plants [34][35][36]. Environmental factors influencing HM bioavailability in the soil include pH, redox state (Eh), ECE, P, OM, salinity, microbial activity and other components, as shown in Table 1 [37][38][39]. The process of activation and dissolution of As/Cd from the adsorption state on the surface of soil particles and migration to the rice root surface is crucial to determining their bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, progress has been achieved to understand the geochemical cycling and translocation of As and Cd from soil to plants [34][35][36]. Environmental factors influencing HM bioavailability in the soil include pH, redox state (Eh), ECE, P, OM, salinity, microbial activity and other components, as shown in Table 1 [37][38][39]. The process of activation and dissolution of As/Cd from the adsorption state on the surface of soil particles and migration to the rice root surface is crucial to determining their bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…So far, As-transforming microbes and As-related genes have been widely investigated in various natural environments, including polluted and pristine soils 27 , 28 , terrestrial geothermal springs 29 31 , wetlands 32 , 33 , pelagic oxygen-deficient zones 34 , groundwater 35 , etc. For example, metagenomic and metatranscriptomic analyses revealed that Aquificae were the key players for the arsC -based detoxification in Tengchong geothermal springs 29 .…”
Section: Introductionmentioning
confidence: 99%
“…So far, As-transforming microbes and As-related genes have been widely investigated in various natural environments, including polluted and pristine soils 27,28 , terrestrial geothermal springs [29][30][31] , wetlands 32,33 , pelagic oxygen-deficient zones 34 , groundwater 35 , etc. For example, metagenomic and metatranscriptomic analyses revealed that Aquificae are the key players for the arsC-based detoxification in Tengchong geothermal springs 29 .…”
Section: Introductionmentioning
confidence: 99%